PENERAPAN APLIKASI TELUNJUK SAKTI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN WONOGIRI - Zanana Utamy; Tri Murwaningsih; Anton Subarno (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2021)
This research aims to determine implementation of Telunjuk Sakti application at Department Of Population And Civil Registration Of Wonogiri Regency. This type of research is qualitative descriptive with a case study approach. The research was conducted at Department Of Population And Civil Registration Of Wonogiri Regency. For sampling using purposive sampling technique and snowball sampling. Data collection techniques with observations, interviews and documents. The validity of the data is obtained by triangulating sources and method. Data analysis techniques use interactive model data analysis            .The result of this research is: 1) the implementation of the Telunjuk Sakti application at the Population and Civil Registration Office of Wonogiri Regency includes: a) Planning, b) Socialization, c) Implementation, and d) Results and evaluation. 2) the implementation of the Telunjuk Sakti application at the Population and Civil Registration Office of Wonogiri Regency has several obstacles including: a) blank spot area, b) inadequate facilities and infrastructure, c) low human resource capabilities, d) Telunjuk Sakti application server often has problems, and, 3) erfforts to overcome the obstacles that occur include: a) installing internet network amplifiers, b) make a budget proposal, c) conducting training and technical guidance, and d) repairing servers on the Telunjuk Sakti application.